2018
DOI: 10.1136/bcr-2018-226818
|View full text |Cite
|
Sign up to set email alerts
|

Case of keratoacanthoma centrifugum marginatum treated with acitretin

Abstract: Keratoacanthoma centrifugum marginatum (KCM) is a rare variant of keratoacanthoma (KA), characterised by a progressively expanding tumour with a lack of spontaneous remission and significant scarring. KCM has been reported previously in less than 50 cases worldwide. We present the case of a large solitary KCM on the right shin of a 71-year-old woman. This was treated successfully with oral acitretin for 16 months with sustained remission at 24 months. Our case provides further supporting evidence for acitretin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Several authors reported successful treatment with oral retinoids for KCM. In English‐based literature, to date, nine cases (including our patient) had good therapeutic response to retinoids, either etretinate, acitretin or isotretinoin, dose ranging from 0.5 to 1 mg/kg body weight 5,7‐12 . Our patient had a good and prompt response to acitretin.…”
Section: Discussionmentioning
confidence: 64%
“…Several authors reported successful treatment with oral retinoids for KCM. In English‐based literature, to date, nine cases (including our patient) had good therapeutic response to retinoids, either etretinate, acitretin or isotretinoin, dose ranging from 0.5 to 1 mg/kg body weight 5,7‐12 . Our patient had a good and prompt response to acitretin.…”
Section: Discussionmentioning
confidence: 64%
“…The differential for cutaneous annular lesions in the elderly includes tinea corporis, sarcoidosis, keratoacanthoma centrifugum marginatum (KCM), actinic granuloma, and GA. Many believe KCM to be a low-grade SCC that can recur but not metastasize [ 5 ]. Features of KCM are notable hyperkeratotic borders and the development of central atrophic scars.…”
Section: Discussionmentioning
confidence: 99%
“…There is not a well‐defined therapeutic protocol probably due to the low incidence of this disease (Sung et al, ). Some cases treated with oral retinoids (Acitretin, Etretinate or Isotretinoin in doses between 0.5 and 1 mg/kg/day) with a good response (Georgescu et al, ; Mehrtens, de la Hera, & Shankar, ) have been reported. One case without response oral retinoids has been successfully treated with wide local excision (Das et al, ).…”
Section: Discussionmentioning
confidence: 99%